Is there any relationship between poor menstrual hygiene management and anemia? - A quantitative study among adolescent girls of the urban slum of Madhya Pradesh - Surya Bali; Sembagamuthu Sembiah; Akanksha Jain; Yash Alok; Jayeeta Burman; Darshan Parida (Wolters Kluwer Medknow Publications, 2021)
Background: Anemia and poor menstrual hygiene practices have a considerable impact on all aspects of an adolescent girl's life. There is a dire need for evidence on the burden and its association to provide actionable preventive measures. Objective: The objective of this study is to explore the magnitude and association between poor Menstrual Hygiene Management (MHM) practices and anemia. Materials and Methods: A cross-sectional study conducted among 393 adolescent girls of the urban slum of Bhopal (June 2017-July 2018). Hemoglobin (Hb) was determined by a portable Hb meter (HemoCue). Logistic regression analysis was done to find out if there is any association between poor MHM practices and anemia. Results: The present study found the prevalence of anemia as 38.7% among which 65.1%, 31.5%, and 3.2% were suffering from mild, moderate, and severe forms of anemia, respectively, and 87.3% were practicing poor MHM. Logistic regression found that the MHM, bleeding during menstruation, religion, educational status, and nutritional status of adolescents were significant factors associated with anemia. Conclusion: The study concluded that there is a significant association between poor MHM and anemia. Concerted convergent actions focusing on the provision of awareness regarding MHM and sanitary facilities to maintain proper menstrual hygiene are needed to reduce the burden of anemia.